PENGARUH LATIHAN KOORDINASI MATA-KAKI-TANGAN TERHADAP KEMAMPUAN BACKSPIN SERVICE ATLET TENIS MEJA SMA OLAHRAGA PEKANBARU - Jumhaini, Jumhaini; Ramadi, Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this reserach was to determine the effect of eye-foot-hand coordination training on the backspin service ability of table tennis athletes at SMAN Sports Pekanbaru. This research was conducted at Yossudarso street no 103, coinciding with table tennis at SMAN Olahraga Pekanbaru. This research was conducted in June - July 2019 with a frequency of 3x a week (Monday, Wednesday and Saturday) using the experimental method. Based on statistical data analysis, there is a pre-test average of 35.33 and a post-test average of 47.33, the difference in numbers increases or increases by 3.41. And based on the t test analysis yields t count of 8.630 and t table 2.015. It means that tcount> ttable, it can be concluded that the Cardiorespiratory Endurance of athletes has an effect on the eye-ankle coordination training needed to support the frequency when doing exercises in increasing the results of Backspin Service Ability. Based on the findings and processing of the data above, it can be concluded as follows: there is an effect of eye-accomplice coordination training (X) on the Ability of Backspin Service (Y) for Table Tennis athletes at SMA Olahraga Pekanbaru.Key Words: Effect of Eye-Foot-Hand Coordination Exercise, Backspin Service,Table Tennis